FRI0245 Abatacept retention rates and prognostic factors of retention in patients with rheumatoid arthritis: 2-year results from the real-world action study. (15th June 2017) - Alten, R; Lorenz, H-M; Mariette, X; Nüßlein, H; Galeazzi, M; Navarro, F; Chartier, M; Elbez, Y; Rauch, C; Bars, M Le
Abstract : Background: The ACTION (NCT02109666 ) study was designed to provide prospective, real-world data on abatacept (ABA) retention in patients (pts) with RA. Objectives: To assess the retention rate and to identify prognostic factors of ABA retention in the overall ACTION population and by treatment line over 2 yrs. Methods: ACTION is a 2-yr, international, observational study of pts with RA who initiated IV ABA as first- or as second-/further-line biologic therapy in routine clinical practice. Biologic-naïve and biologic-failure pts were enrolled during three periods between May 2008 and December 2013. The primary endpoint was crude ABA retention rate over 2 yrs (Kaplan–Meier plot). Prognostic factors (p≤0.2) from univariate analyses with no colinearity, clinically relevant variables and known risk factors were entered into a multivariate model; factors with p≤0.1 were retained by backward selection. EULAR response was compared by Fisher's exact test. Results: In the ACTION cohort, 2350/2364 enrolled pts were evaluable for analysis; 673 (28.6%) were biologic naïve and 1677 (71.4%) had failed biologic treatment. Most biologic-failure pts (56.6%) had previously received ≥2 biologics. Some expected differences in baseline characteristics were observed between groups; mean (SD) RA duration was shorter (7.2 [8.2] vs 12.1 [9.1] yrs; p<0.001), more pts had RA for ≤2 yrs (35.7 vs 9.0%; p<0.001) and fewer pts had radiographic erosions (58.2 vs 71.5%; p<0.001) for biologic-naïve vs biologic-failure pts. At Yr 2, the overall retention rate was 47.9% (95% CI 45.7, 50.0). The retention rate was higher in biologic-naïve vs biologic-failure pts (54.5 vs 45.2%; p<0.001) and in pts with 1 vs ≥2 previous biologics (Fig). Reasons for discontinuation were comparable between groups; main reasons were lack of efficacy (61.4 vs 67.7%) and safety (21.3 vs 21.2%). RF and anti-citrullinated protein antibody (ACPA) seropositivity were prognostic factors for higher retention in biologic-naïve (p=0.030) and biologic-failure pts (p=0.028); other positively impacting factors were diabetes mellitus (p=0.044; biologic naïve); geographic location (p<0.001; biologic naïve) and ABA combination therapy (p<0.001; biologic failure). Only Pt Global Assessment (p=0.009; biologic failure) predicted lower retention. Among pts continuing ABA, a greater proportion of biologic-naïve vs biologic-failure pts had a good/moderate EULAR response (90.7 vs 81.6%; p=0.005) and RF/ACPA seropositivity was associated with a better response (p=0.002). There were no new safety signals. Conclusions: In this first prospective, international, non-interventional research evaluating the long-term IV abatacept retention, RF and ACPA seropositivity were predictors of 2-yr higher retention and better outcomes. Higher retention rates may be achievable with earlier vs later initiation of abatacept treatment, consistent with prior findings from a pooled analysis of EU and Canadian registries. 1 References: Iannone F et al. Clin Rheumatol (2016): doi:10.1007/s10067–016–3505–5. Disclosure of Interest: R. Alten Grant/research support from: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, H.-M. Lorenz Consultant for: AbbVie, Bristol-Myers Squibb, Roche-Chugai, UCB, MSD, GSK, SOBI, Medac, Novartis, Janssen-Cilag, AstraZeneca, Pfizer, Actelion, X. Mariette Grant/research support from: Biogen, Pfizer, UCB, Consultant for: Bristol-Myers Squibb, LFB, Pfizer, GSK, UCB, H. Nüßlein Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Roche, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Roche, M. Galeazzi: None declared, F. Navarro Grant/research support from: Pfizer, MSD, AbbVie, Bristol-Myers Squibb, Roche, Consultant for: Pfizer, MSD, Roche, UCB, AbbVie, Bristol-Myers Squibb, Jansen, Lilly, Speakers bureau: Pfizer, MSD, Roche, UCB, AbbVie, Bristol-Myers Squibb, M. Chartier Employee of: Bristol-Myers Squibb, Y. Elbez: None declared, C. Rauch Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Le Bars Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb